Effect of a Low-Dose Contraceptive Patch on Efficacy, Bleeding Pattern, and Safety: A 1-Year, Multicenter, Open-Label, Uncontrolled Study. (December 2014) - Wiegratz, Inka; Bassol, Susana; Weisberg, Edith; Mellinger, Uwe; Merz, Martin
This Phase III, uncontrolled, open-label, multicenter study was conducted to investigate the contraceptive efficacy, bleeding pattern, and cycle control of a novel once-a-week contraceptive patch, delivering low-dose ethinyl estradiol (EE) and gestodene (GSD) at the same systemic exposure seen after oral administration of a combined oral contraceptive containing 0.02 mg EE/0.06 mg GSD. Participants were women aged 18 to 35 years, all of whom received the EE/GSD patch for 13 cycles each of 21 treatment days (one patch per week for 3 weeks) followed by a 7-day, patch-free interval. The primary efficacy variable was the occurrence of unintended pregnancies during the study period as assessed by life table analysis and the Pearl Index. Secondary efficacy variables were days with bleeding during four 90-day reference periods and during 1 treatment year, bleeding pattern, and cycle control. The Kaplan-Meier probability of contraceptive protection after 364 treatment days was 98.8% and the adjusted Pearl Index was 0.81. The percentage of participants with intracyclic bleeding/spotting decreased over time, from 11.4% to 6.8% in cycles 1 and 12, respectively. Almost all participants (range: 90.8%-97.6%) experienced withdrawal bleeding across the study period. Compliance was very high (mean: 97.9%; median: 100%). The most frequent adverse events were headache (9.5%) and application site reaction (8.5%); no clinically significant safety concerns were observed. Results suggest the EE/GSD patch is highly effective in preventing pregnancy. Menstrual bleeding pattern was favorable and within the ranges expected of a healthy female population. The patch was well tolerated and treatment compliance was high.